Ghanaian Prosperity Preaching - Ossom-Batsa, George; Gatti, Nicoletta (World Christianity and Covid-19: Looking Back and Looking Forward, 2023)
The notion that suffering cannot be part of the Christian life has become pervasive in contemporary Ghanaian Christianity. Proponents of the Prosperity Gospel teach that suffering such as poverty, disease, failure, and hardships are not part of God’s plan but rather signs of lack of faith and even sin. Their preaching re-packages retributive theology, which characterizes many books of the Tanak. However, the personal and social experience of the silence of God before “unjust” suffering has generated texts—such as Psalm 73, the book of the prophet Habakkuk, and above all the book of Job—which express a challenge to this commonly held theology and to any reassuring theology. In Ghanaian Christianity, where God is identified with prosperity, miracles, success, wealth, absence of pain, disease, and death, the health, social, and economic crises provoked by the COVID-19 pandemic present a hermeneutic challenge and a biblical-theological question. Where is God in human suffering? Against this background, the article proposes an intercultural and pragmatic reading of the theological debate between Job and his friends, between experiential and retributive theology, to reconstruct a new image of God, capable of offering hope to Ghanaians in the COVID-19 pandemic.
paid